Construction of complete chloroplast genome of the endemic species Paphiopedilum delenatii Guillaumin (1924) of Vietnam - Thanh Diem, Nguyen; Ly, Le Thi; Thuan Anh, Nguyen Huu; Thanh Cong, Nguyen; Huyen Trang, Vu Thi (Vietnam Journal of Biotechnology, 2020)
Chloroplasts and mitochondria are organelles that have their own genome in a cell. The chloroplast genome provides information on the evolutionary relationship and species identification, valuable markers for transgenic plants, and cloning plants, etc. The application of Next Generation Sequencing has improved the chloroplast genome sequencing. However, the assembly process of chloroplast genome is quite complicated due to the need of different complex bioinformatics tools, high configuration computer and laborous. Here we configured the process of assembling the chloroplast genome of Paphiopedilum delenatii. The assembled chloroplast genome was 160,955 bp in length, including a large and a small single copy region (LSC, SSC) separated by a pair of inverted repeats (IR). Total genes were 130 genes, GC content is 35.6%. Genome data was mapped and registered in GenBank under accession number MK463585. The optimal parameters for genome assembling were recommended. This study not only provided information for conservation of the Vietnam endemic Paphiopedilum delenatii species but also supported the genome assemble researches which could be applied on other subjects.